Effect of Covid-19 on Organizational Performance. A case of Seawork Fish Processors (SFP), Walvis Bay, Namibia. - Haileka, Klaudia N.; Johannes, Marius; Zvarewashe, Braine (Journal of Business and Strategic Management, 2025)
Purpose: The purpose of the study was to assess effect of Covid-19 on organizational performance at Seawork Fish Processor in Walvis Bay, Namibia. Methodology: The study employed mixed-methods research design, gathering quantitative data from SFP's financial reports and questionnaires, complemented by qualitative data from face-to-face interviews. A total sample size of 338 respondents was used, based on a widely utilized descriptive study sample size estimation formula. Data from the questionnaires were captured using Statistical Package for the Social Sciences (SPSS) and Microsoft Excel. After data capture, the researcher analyzed the data using tables, graphs, and pie charts. Financial ratios were applied to evaluate the impact of COVID-19 on organizational performance alongside the questionnaire responses. Findings: The results revealed that SFP's profitability and efficiency in producing returns for shareholders suffered in 2019 but started to improve in 2020 and 2021. Based on the study's findings, companies could implement agile techniques, such as supply chain optimization, cost-cutting measures, and manufacturing process optimization, to efficiently manage comparable crises. It was also determined that investing in digital transformation and comprehensive risk management procedures enhances resilience and adaptation in the face of future challenges. Unique Contribution to Theory, Practice and Policy: The study offered empirical insights into how a fish processing company in Namibia responded to a global crisis, which advanced the idea of organizational resilience. It provided practical recommendations for firms like to adapt operations, mitigate risks, and enhance performance during disruptions. The findings were a valuable resource for industry associations, business consultants, and policymakers seeking to improve crisis navigation tactics from a policy viewpoint.